Comparison of fracture behavior of defective armchair and zigzag graphene nanoribbons. (March 2019) - Zhang, Ji; Ragab, Tarek; Basaran, Cemal
Molecular dynamics simulations of armchair graphene nanoribbons and zigzag graphene nanoribbons with different sizes were performed at room temperature. Double vacancy defects were introduced in each graphene nanoribbon at its center or at its edge. The effect of defect on the mechanical behavior was studied by comparing the stress–strain response and the fracture toughness of each pair of pristine and defective graphene nanoribbon. Results show that the effect of vacancies in zigzag graphene nanoribbon is more profound than in armchair graphene nanoribbon. Also, the effect of double vacancy defect on the ultimate failure stress is greater in zigzag graphene nanoribbons than in armchair graphene nanoribbon due to bond orientation with respect to loading direction. Strength reduction can be as high as 17.5% in armchair graphene nanoribbon with no significant difference between single and double vacancies, while for zigzag graphene nanoribbon, the strength reduction is up to 30% for single vacancy and 43% for double vacancy defects. It is observed that for zigzag graphene nanoribbon with double vacancy at the edge, the direction of the failure plane is oriented at ±30° with respect to the loading direction while it is always perpendicular to the direction of loading in armchair graphene nanoribbon. Results have been verified through studying the fracture toughness parameters in each case as well.